2018
DOI: 10.1016/j.bulcan.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Administration précoce de témozolomide après chirurgie chez des patients ayant un glioblastome de mauvais pronostic : étude de faisabilité

Abstract: Early postsurgical temozolomide treatment prior to standard adjuvant therapy for poor prognosis glioblastoma patients in our small prospective series presents toxicity and survival similar to those published in the literature for the general population of glioblastoma. These encouraging results should be confirmed by a multicentric study comparing this regiment with the standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Finally, a small pilot feasibility study showed that a single additional cycle of 5 days of 200 mg/m 2 TMZ given in the 4-week interval from surgery to standard chemoradiation was safe, feasible and associated with 71% overall survival rate at 18 months. 27 Conversely the clinical efficacy of TMZ administered prior to surgery, 28 or prolonged TMZ administered prior to and delaying chemoradiation 29 has not demonstrated efficacy. However, there have been no randomised trials demonstrating the efficacy of neoadjuvant chemotherapy compared with the current standard of care, therefore, this experimental arm of MAGMA seeks to answer this question.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a small pilot feasibility study showed that a single additional cycle of 5 days of 200 mg/m 2 TMZ given in the 4-week interval from surgery to standard chemoradiation was safe, feasible and associated with 71% overall survival rate at 18 months. 27 Conversely the clinical efficacy of TMZ administered prior to surgery, 28 or prolonged TMZ administered prior to and delaying chemoradiation 29 has not demonstrated efficacy. However, there have been no randomised trials demonstrating the efficacy of neoadjuvant chemotherapy compared with the current standard of care, therefore, this experimental arm of MAGMA seeks to answer this question.…”
Section: Introductionmentioning
confidence: 99%
“…Despite standard treatments consisting of surgery, postoperative radiotherapy, and chemotherapy with temozolomide. Patient survival remains poor, which is mainly attributed to tumor inherent radio-and chemoresistance (14,15).…”
mentioning
confidence: 99%